Ethnobotany of three sea grass species from Port Blair, a step towards its conservation in Andaman Islands - Mohammed Naufal PJ; G Padmavati (Journal of Tropical Life Science, 2021)
Ethno-phycology is the study of the relationships of human society to flora and its ecosystem. In the marine world, ethno-biology is a thriving area of research which have yielded valuable ethno-biological knowledge. The main goal of the present study was to understand the effect of abiotic factors as well as the natural and anthropogenic disturbances that shape seagrass community in Andaman Island and to reveal the knowledge of the local people, about the significance of seagrass habitat and its conservation. The qualitative study on distribution of seagrasses in Chidiyatapu (11° 29' 30" to 11° 30' 34" N and 92° 35' 10" to 92° 42' 30" E) was carried out during December2012 to February 2013. A total of three seagrass species such as Thalassia hempirichi (Ehrenberg) Ascherson, 1871, Halodule uninervis  (R.Brown) J.D.Hooker 1858, Halophila ovalis (Forsskål) Ascherson 1882, where identified. Among them, T. hempirichi, and H. ovalis found in this study was reported to have the ethno-medicinal value from west coast of India. As a part of the study, the  semi-structured survey was carried out among the local coastal people to analyse the Traditional Ecological Knowledge (TEK). The survey has revealed the  unawareness of  coastal residents about the medicinal, nutritional as well as conservational values of seagrasses. An effective implementation has to be taken to make them aware that seagrasses are fundamental components of healthy marine ecosystems and the local livelihoods that rely on them. The present findings provide the first report on the ethno-phycology of seagrasses from South Andaman Island.